The Effect of Motor Imagery Training on Lower Limb Function in Older Adults: A Systematic Review - Zhang, Mufan; Zhang, Tingran; Zhang, Jiahan; Luo , Jiong (Quality in Sport, 2024)
Background Population aging is a significant trend in China’s development, and the decline in lower limb function in older adults is one of the primary health threats, often leading to falls or injuries. Several studies have applied motor imagery (MI) to improve lower limb function in older adults. However, the benefits of this intervention method for older adults remain to be further explored. Objective This paper systematically reviews the benefits of motor imagery in improving lower limb function in older adults using the International Classification of Functioning, Disability, and Health (ICF) framework. Methods Relevant literature on motor imagery interventions targeting balance ability in healthy older adults was retrieved from four English and three Chinese databases. The content of the literature was analyzed and coded based on the theoretical framework of the ICF. Results A total of 11 studies from 7 countries were included, comprising 11 randomized controlled trials (RCTs) with 758 older adult participants. Interventions included MI alone or combined with physical exercise, and intervention settings encompassed laboratories, communities, hospitals, and homes. Outcome measures included motor function, postural changes and maintenance, gait, and mobility. Conclusion Motor imagery interventions and their combination with other intervention methods can improve lower limb function and related motor abilities in older adults. However, compared to MI alone, the effects of combined MI interventions on lower limb function in older adults remain inconclusive.